Evidence for a Contribution of ALA Synthesis to Plastid-To-Nucleus Signaling - Czarnecki, Olaf; Gläßer, Christine; Chen, Jin-Gui; Mayer, Klaus F.; Grimm, Bernhard (Frontiers in Plant Science, 2012)
The formation of 5-aminolevulinic acid (ALA) in tetrapyrrole biosynthesis is widely controlled by environmental and metabolic feedback cues that determine the influx into the entire metabolic path. Because of its central role as the rate-limiting step, we hypothesised a potential role of ALA biosynthesis in tetrapyrrole-mediated retrograde signalling and exploited the direct impact of ALA biosynthesis on nuclear gene expression (NGE) by using two different approaches. Firstly, the Arabidopsis gun1, hy1 (gun2), hy2 (gun3), gun4 mutants showing uncoupled NGE from the physiological state of chloroplasts were thoroughly examined for regulatory modifications of ALA synthesis and transcriptional control in the nucleus. We found that reduced ALA-synthesising capacity is common to analysed gun mutants. Inhibition of ALA synthesis by gabaculine (GAB) that inactivates glutamate-1-semialdhyde aminotransferase and ALA feeding of wild-type and mutant seedlings corroborate the expression data of gun mutants. Transcript level of photosynthetic marker genes were enhanced in norflurazon (NF)-treated seedlings upon additional GAB treatment, while enhanced ALA amounts diminish these RNA levels in NF-treated wild-type in comparison to the solely NF-treated seedlings. Secondly, the impact of posttranslationally down-regulated ALA synthesis on NGE was investigated by global transcriptome analysis of GAB-treated Arabidopsis seedlings and the gun4-1 mutant, which is also characterized by reduced ALA formation. A common set of significantly modulated genes was identified indicating ALA synthesis as a potential signal emitter. The overrepresented gene ontology categories of genes with decreased or increased transcript abundance highlight a few biological processes and cellular functions, which are remarkably affected in response to plastid-localised ALA biosynthesis. These results support the hypothesis that ALA biosynthesis correlates with retrograde signalling-mediated control of NGE.